Ứng dụng công nghệ GIS để thành lập bản đồ nhạy cảm trượt lở đất các tỉnh biên giới Tây Bắc Việt Nam - Dần, Nguyễn Tứ; Tuấn, Trần Anh; Lee, Saro (Vietnam Journal of Earth Sciences, 2008)
Application of GIS technology to establish probabilistic landslide susceptibility map in the North West frontier provinces of Vietnam